Pesticide residues in strawberry fruits cultivated under integrated pest management and conventional systems in Cundinamarca (Colombia) - Sánchez, Manuel; López V., David; Fischer, Gerhard; Acuña C., John Fabio; Darghan, Aquiles Enrique (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
Due to the high susceptibility of strawberry fruits to the attack of pests and diseases, a large amount of pesticides is applied during the crop cycle and harvest period. The inadequate use of these substances can generate residuals in agricultural products, which, through intake, pose a risk to human health. The objective of this study was to determine and compare the pesticide residues in strawberry fruits from two different production systems, distributed in the main producing areas of the Cundinamarca Department (Colombia). Eight samples of strawberry crops were collected in four producer municipalities (Guasca, Facatativa, Mosquera and Sibate), two to compare different systems (conventional production vs. production based on the Integrated Pest Management, IPM). Samples at a concentration of 394 molecules were examined by liquid and gas spectrometry. Fisher's exact test was used to determine the association between crop practices and the residual level in fruits. Twenty two different molecules were detected for the samples analyzed, with 37 detection events, of which eight were reported in IPM production systems and 29 in conventional producers. Results revealed a total of two molecules at excessive concentrations after Colombian regulations. Significant differences were found between the two production systems. This is attributable to the producers´ lack of knowledge and understanding about conventional management in Good Agricultural Practices, and the concepts of pesticide restriction period and residuality.